Bioactive polysaccharides from natural resources including Chinese medicinal herbs on tissue repair - Qiu Li; Yiming Niu; Panfei Xing; Chunming Wang (BMC, 2018)
Abstract Background Functional polysaccharides can be derived from plants (including herbs), animals and microorganisms. They have been widely used in a broad of biomedical applications, such as immunoregulatory agents or drug delivery vehicles. In the past few years, increasing studies have started to develop natural polysaccharides-based biomaterials for various applications in tissue engineering and regenerative medicine. Main body We discuss in this article the emerging applications of natural polysaccharides-particularly those derived from Chinese medicine-for wound healing. First, we introduce natural polysaccharides of three natural sources and their biological activities. Then, we focus on certain natural polysaccharides with growth factor-binding affinities and their inspired polymeric tools, with an emphasis on how these polysaccharides could possibly benefit wound healing. Finally, we report the latest progress in the discovery of polysaccharides from Chinese medicinal herbs with identified activities favouring tissue repair. Conclusion Natural polysaccharides with clearly elucidated compositions/structures, identified cellular activities, as well as desirable physical properties have shown the potential to serve as therapeutic tools for tissue regeneration.